Buck-Boost Control of Four Quadrant Chopper using Symmetrical Impedance Network for Adjustable Speed Drive - Saswati Swapna Dash; Byamakesh Nayak (Institute of Advanced Engineering and Science, 2015)
This paper proposes buck-boost capabilities of four quadrant chopper for wide range speed control of DC motor drives using symmetrical impedance network called Z-source network. By controlling the shoot through duty ratio from 0 to 0.5 and non-shoot through techniques, the Z-source four quadrant choppers can produce any desired DC voltage across the DC motor. The switching patterns for both buck and boost operations are presented to achieve four modes of operation of DC motor. As a result, the proposed model will have ride through capability during voltage sags, manage during voltage swells, used in any types of DC voltage sources such as fuel cell and solar cell and improve the reliability by reducing EMI noise. Analysis and simulation results are presented to demonstrate these new findings.